THE MEANING OF KARAENG AT THE DEMOCRACY PARTY IN JENEPONTO REGENCY - A. Tri Arwina Dheafati; Muh. Ridwan Said Ahmad; Hasruddin Nur; Najamuddin; Jumadi (RADJA PUBLIKA, 2025)
This study aims to: 1) To analyze the meaning of the title Karaeng in Jeneponto Regency. 2) To analyze how the Karaeng title affects social structure and leadership. 3) To analyze how the social order with the title of Karaeng in the Regional Elections in Jeneponto. The approach used is descriptive with a qualitative type of research. Data collection through observation, interviews, and documentation. informants, namely 15 people using purposive sampling techniques, with informant criteria including Figures / Traditional Stakeholders; a person with the title of Karaeng; The general public who do not have a karaeng title; local youth leaders/activists; Government officials in the field of culture and politics; Political actor with the title karaeng. Data analysis techniques are data condensation, data modeling and drawing conclusions. The results of the study indicate that: a) The title of karaeng in Jeneponto Regency has a deep philosophical meaning, rooted in royal traditions passed down through generations and reflects the values ​​of honor, wisdom, and social responsibility as a symbol of community identity and status. This title is not only a status symbol, but also a marker of social identity that distinguishes a person's position in society. The values ​​​​inherited in the title reflect the Jeneponto people's outlook on leadership, exemplary behavior, and interpersonal relationships based on respect and justice. b) In the social structure, holders of the karaeng title remain respected and influential, both in formal leadership such as government and non-formal in traditional and social environments, and serve as role models in maintaining community harmony. c) The meaning of the karaeng title in the regional elections in Jeneponto is seen from its still strong role in shaping the direction of community political support. This title is a symbol of trust and social influence that is able to mobilize community loyalty, even though now society is starting to judge prospective leaders not only by their titles, but also by their personal abilities and integrity in leadership.